The costs of elite-oriented multi-stakeholder forums to address deforestation: the case of the Green Municipalities Program in the Brazilian Amazon - Londres, M.; Larson, A.M.; Sarmiento Barletti, J.P. (2021)
This article examines the Green Municipalities Program (Programa Municípios Verdes – PMV) – a major multi-stakeholder forum designed to combat deforestation – in Pará state in the eastern Brazilian Amazon. We qualitatively analyzed in-depth interviews with 39 people with different perspectives: respondents with deep knowledge of the context but no direct involvement in the program, organizers of the program, diverse program participants, and diverse non-participants. We interrogated the PMV’s strategy to address deforestation by collaborating directly with the powerful sectors that are driving it, while excluding indigenous and grassroots organizations from the process. The results reinforce the critique of ‘anti-politics’ approaches that prioritize technical solutions that focus on the consequences of environmental problems (such as deforestation) without addressing their underlying causes. The research highlights the risks of multi-stakeholder processes in highly unequal contexts that do not question the power of elites, and questions the legitimacy of initiatives that gain wide acclaim but are perceived locally as unjust.